YOUNG PEOPLE'S VISIONS FOR LIFE IN THE COUNTRYSIDE IN LATIN AMERICA - De La Vega-Leinert, A. Cristina; Kieslinger, Julia; Jimenez-Moreno, Marcela; Steinhauser, Cornelia (Geographical Review, 2021)
Abtract Young people steer their life trajectories against the backdrop of profound transformations of rurality. They are considered protagonists in the present and future of rural areas; however, their experiences and perspectives on life in, and away from, the countryside have been scarcely acknowledged in academia. Considering conceptual thoughts on new mobilities, place-based belonging, and new ruralities, we argue that young people are a highly dynamic and continually reassessing group. In four case studies realized independently in Argentina, Bolivia, Ecuador, and Mexico, we closely involved young people with multiple participative methods to express their perceptions, concerns, and demands. We experiment on ways to integrate our insights for future comparative studies. Beyond the diversity in local contexts, we found convergences in young people's visions, which motivate them to stay or leave, with wider implications for the sustainability of rural places. "Living in between" thereby encapsulates multifaceted hybrid possible countrysides away from constraining dichotomic views.
CRIS-Team WoS Importer:2021-06-25